Social strains of globalization in India : case examples - Taber, Merlin A; Batra, Sushma, 1953- (New Delhi : New Concepts, 1996)
Contributed articles
Keywords: Social change -- India; Women -- India; People with social disabilities -- India; Social services -- India; Globalization; Medical social work -- India; India -- Social conditions -- 1947-